Pelaksanaan Modifikasi Permainan Kecil dalam Pembelajaran Penjasorkes - Ever Sovensi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2018)
The purpose of this study is to know the description of the implementation of modification learning penjasorkes. This research uses a descriptive method. The study population was 121 people. Sampling was done by Purposive random sampling, got sample amounted to 58 people. The instrument used to collect data is Questionnaire or questionnaire using Guttman scale. Data were analyzed by using frequency distribution formula in percentage form. The results of the study are as follows: the level of achievement of student's motivation in State Elementary School 27 is in very good classification, that is with the achievement of respondent answer reach 85 percent. The level of teaching method achievement in the implementation of small game modification in the learning of penjasorkes at the Pangian State Elementary School is in a very good classification, with an achievement rate of 85.86 percent. The level of achievement of the facilities and infrastructure for the implementation of small game modification in the learning of penjasorkes in Public Elementary School 27 Pangian is in good classification, that is with the level of respondents achievement reaches 74.65 percent Keywords: Modification, Penjasorkes